Romesh Chander Dutt’s ‘Romesh Chander Dutt- The Economic Historey of India Under British Rule From the Rule of the British Power in 1757 to the Accession of Queen Victoria in 1857’: A Source for Understanding the Early Nationalist Economic Perception: An In-depth Study of Romesh Chander Dutt's Contribution to Early Nationalist Economic Perception in Colonial India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The most significant historical contribution of the early nationalist leaders was that theyoffered an economic critique of colonialism. The main thrust of this economic nationalism was on Indianpoverty created by the application of the classical economic theory of free trade. Three names areimportant to remember in this respect Dadabhai Naoroji, a successful businessman, JusticeM.G.Ranade and Romesh Dutt, a retired ICS officer, who published The Economic History of India in twovolumes (1901-03). The present paper is an effort to have a peep into the authoritative work of RomeshDutt. Romesh Dutt was born (b. 1848 d. 1909), was litterateur, politician and one of the greatestintellectuals of his time. He was a distinguished civil servant, spokesman of educated, political leader ofa liberal school, historian and creative writer. He became president of Indian national congress in 1899.He also taught Indian history in London University. On his return from London, he served Baroda stateRevenue Minister for three years. He produced valuable books on economics, history and IndianCivilization and also wrote some Bengali Novels. Peasantry of Bengal, Famines in India, History ofCivilization in Ancient India, England and India and Economic History of India in the Victorian Age.Service to the motherland was the driving force behind all his varied activities.